2017
DOI: 10.1039/c6ce02327d
|View full text |Cite
|
Sign up to set email alerts
|

Bulk graphanes synthesized from benzene and pyridine

Abstract: The discovery of graphene stimulated an intensive search for its analogs and derivatives. One of the most interesting derivatives is hydrographene called graphane. Calculations indicate that bulk graphane is thermodynamically more favorable than all CH hydrocarbons including benzene. At the same time, pressureinduced polymerization of hydrocarbons and their derivatives at room temperature leads to the formation of amorphous products or poorly ordered one-dimensional products such as polyacetylene and benzene-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 43 publications
5
35
1
2
Order By: Relevance
“…A completely different approach was used by Brazhkin et al., who prepared graphane by high temperature (700–1200 K) and high pressure (<10 GPa) synthesis from benzene. The synthesis also allowed the production of nitrogen‐doped graphane by the use of a benzene/pyridine mixture …”
Section: Synthesis Of Graphene Derivativesmentioning
confidence: 72%
See 1 more Smart Citation
“…A completely different approach was used by Brazhkin et al., who prepared graphane by high temperature (700–1200 K) and high pressure (<10 GPa) synthesis from benzene. The synthesis also allowed the production of nitrogen‐doped graphane by the use of a benzene/pyridine mixture …”
Section: Synthesis Of Graphene Derivativesmentioning
confidence: 72%
“…The synthesis also allowed the production of nitrogen-doped graphane by the use of a benzene/pyridine mixture. [76] In contrast, the wet chemistry processes based on dissolving metals,s uch as alkali metals,i nl iquid ammonia, whichs erve as as ource of solvated electrons, prove to be very useful in the production of highly hydrogenated graphenes by Birch-type reactions. [77] It has been demonstratedt hat single-layer graphene is hydrogenated uniformly,b ut graphene with more layers and sealed edges is not,w hich supports the idea that hydrogenation occurs from the edges of graphene by intercalation of alkali metal into the structure, where the defects are located.…”
Section: Sulfur Functionalities On Graphenementioning
confidence: 99%
“…[2c] Recently,i tw as reported that aniline forms diamond-like polyaniline under external pressure and the hydrogen bond between the NH 2 groups is believed to be responsible for better crystallinity. [4] Ther eaction mechanism of these pressure-induced polymerizations (PIPs) was explored from various perspectives. [4] Ther eaction mechanism of these pressure-induced polymerizations (PIPs) was explored from various perspectives.…”
mentioning
confidence: 99%
“…[2d] Besides the one-dimensional structure, the graphane structure was also obtained by compressing the aromatics under high-pressure and high-temperature conditions. [4] Ther eaction mechanism of these pressure-induced polymerizations (PIPs) was explored from various perspectives. Va rious possible connections between benzene molecules were theoretically proposed, and the energies of the formed dimers were examined to evaluate the corresponding reactions.…”
mentioning
confidence: 99%
“…При этом учитывались различные конфигурации веществ в зависимости от соединения бензольных колец. Предыдущие исследования касались фазовой диаграммы, РТусловий диссоциации и определения стабильных фаз бензола при давлениях до 30 ГПа (Thiery, Leger, 1988;Ciabini et al, 2005;2007;Kondrin et al, 2017;Chanyshev et al, 2018). Теоретический расчет фазовых преобразований бензола проведен до давлений 200 ГПа (Wen et al, 2011).…”
unclassified